Dukungan Sosial pada Anak dengan Autisme Dari Orang Tua yang Memiliki Lembaga Pendidikan dan Pelayanan Anak Bekebutuhan Khusus (ABK) - Hasanah, Syamya Nor; Noor, Irfan; Komalasari, Shanty (Jurnal Al-Husna, 2020)
Autism is a developmental disorder that result in a children growth does not develop optimally, both in terms of communication, social interaction motor, sensory and emotion, so that children needs social support from people around them, especially parents in doing daily activities. Social support is divided into four type, that is emotional support, esteem support, tangible or instrumental support, and informational support. Type of research using case study with a qualitative approach. The research subject were father and mother who have autism children and have services for children with special needs. Data collection techniques using observation, interview, and documentation. Data analysis techniques using data collection techniques, data reduction data presentation and drawing conclusions. The results show that the social support which is given by parents including emotional support in the form of affection, care and concern, listening and trusting, then esteem support in the form giving reward for positive things done by children, informational support in the form of finding out and giving information that the children needs, tangible or instrumental support in the form of providing materials and facilities, provides job assistance or services and spending time.